BisAMP: a web-based pipeline for targeted RNA cytosine-5 methylation analysis - Bormann, Felix; Tuorto, Francesca; Cirzi, Cansu; Lyko, Frank; Legrand, Carine (Methods, 2019)
RNA cytosine-5 methylation (m5C) has emerged as a key epitranscriptomic mark, which fulfills multiple roles in structural modulation, stress signaling and the regulation of protein translation. Bisulfite sequencing is currently the most accurate and reliable method to detect m5C marks at nucleotide resolution. Targeted bisulfite sequencing allows m5C detection at single base resolution, by combining the use of tailored primers with bisulfite treatment. A number of computational tools currently exist to analyse m5C marks in DNA bisulfite sequencing. However, these methods are not directly applicable to the analysis of RNA m5C marks, because DNA analysis focuses on CpG methylation, and because artifactual unconversion and misamplification in RNA can obscure actual methylation signals. We describe a pipeline designed specifically for RNA cytosine-5 methylation analysis in targeted bisulfite sequencing experiments. The pipeline is directly applicable to Illumina MiSeq (or equivalent) sequencing datasets using a web interface (https://bisamp.dkfz.de), and is defined by optimized mapping parameters and the application of tailored filters for the removal of artifacts. We provide examples for the application of this pipeline in the unambiguous detection of m5C marks in tRNAs from mouse embryonic stem cells and neuron-differentiated stem cells as well as in 28S rRNA from human fibroblasts. Finally, we also discuss the adaptability of BisAMP to the analysis of DNA methylation. Our pipeline provides an accurate, fast and user-friendly framework for the analysis of cytosine-5 methylation in amplicons from bisulfite-treated RNA.
Gesehen am 17.01.2022
Online publiziert am 24. Oktober 2018